Development of Clindamycin-Loaded Biodegradable Polymeric Films for Localized Wound Healing Applications - Saara Naaz; T. Sowmya; T. Mangilal; Afreen Banu; K. Tharun kumar (International Journal of Pharmacy and Analytical Research, 2026)
This work intended to create biodegradable polymeric films loaded with clindamycin for localized wound healing applications with natural polymer composites. Five formulations (F1–F5) were developed using the solvent casting method and comprehensively assessed for their physicochemical, mechanical, antibacterial, and in vitro drug release properties. All films displayed consistent thickness, negligible weight fluctuation, sufficient folding durability, and a surface pH suitable for skin, thereby affirming reproducible production and cutaneous safety. The moisture content, moisture absorption, and swelling index increased with elevated polymer concentrations, signifying enhanced hydration capacity crucial for wound healing. Mechanical assessment indicated a notable improvement in tensile strength and elongation, guaranteeing flexibility and durability appropriate for wound dressing applications. The drug content in all formulations was within acceptable limits, indicating consistent distribution of the medicine. In vitro release tests indicated regulated and prolonged diffusion of clindamycin, with formulation F5 exhibiting the most advantageous release profile. The antibacterial assessment demonstrated efficient suppression of Staphylococcus aureus, which aligned closely with the release characteristics. The release kinetics primarily adhered to the Higuchi model, signifying diffusion-controlled drug transport. Accelerated stability experiments validated the physical and functional stability of the optimized formulation. Clindamycin-loaded biodegradable polymeric films exhibited significant potential as effective localized antibacterial wound treatments.